Broken K Pueblo - Hill, James N. (University of Arizona Press, 2024)
This report presents an analysis of a prehistoric Pueblo community in structural, functional, and evolutionary terms; it is a sequel to William A. Longacre's Archaeology as Anthropology. The emphasis is on social organization (including the patterning of community activities) and on understanding changes in this organization in terms of adaptive responses to a shifting environment.